2013
DOI: 10.1002/esp.3356
|View full text |Cite
|
Sign up to set email alerts
|

Wood dynamics in upland streams under different disturbance regimes

Abstract: This paper presents reach scale large wood (LW) budgets of 12 upland streams in the Okanagan Basin of British Columbia. The study included 100 m long reaches at three wildfire sites and three undisturbed sites in the Interior Douglas‐fir (IDF) biogeoclimatic zone, and three recent Mountain Pine Beetle (MPB) infestation sites and three undisturbed sites in the Montane Spruce (MS) zone. Detailed information on wood recruitment, output and storage were obtained from repeated annual surveys. Recruitment from the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Therefore, the pioneering observations from Greece and Portugal suggest low instream wood abundance in small streams across the European Mediterranean region, which is generally characterized by a long history of human influence on land cover, including on riparian corridors (Cooper et al, ). For comparison with streams of similar dimensions draining arid and semiarid environments but with a colder climate and dominant coniferous forests, higher average LW volumes of 43.1 m 3 /ha were documented in northern Wyoming (Nowakowski & Wohl, ), and much higher LW frequencies (14–88 LW/100 m) and volumes (26–290 m 3 /ha) were reported from British Columbia (King et al, ). However, our measured LW volume was low, similar to the median values (15.8 and 21.7 m 3 /ha) obtained from two study regions of New Mexico recently affected by high‐magnitude floods and debris flows (Wohl et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pioneering observations from Greece and Portugal suggest low instream wood abundance in small streams across the European Mediterranean region, which is generally characterized by a long history of human influence on land cover, including on riparian corridors (Cooper et al, ). For comparison with streams of similar dimensions draining arid and semiarid environments but with a colder climate and dominant coniferous forests, higher average LW volumes of 43.1 m 3 /ha were documented in northern Wyoming (Nowakowski & Wohl, ), and much higher LW frequencies (14–88 LW/100 m) and volumes (26–290 m 3 /ha) were reported from British Columbia (King et al, ). However, our measured LW volume was low, similar to the median values (15.8 and 21.7 m 3 /ha) obtained from two study regions of New Mexico recently affected by high‐magnitude floods and debris flows (Wohl et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the postfire toppling increase is supported by research in streams in British Columbia, which has shown that fires increase the recruitment rate by an order of magnitude or more [ King et al ., ], and is conservative relative to toppling rates measured by Bendix and Cowell []. The period of pulsed wood increase is followed by a 50 year period in which no toppling or riparian recruitment occurs as the regenerating forest matures.…”
Section: Simulationsmentioning
confidence: 99%
“…Quantitative information on the volume of wood required to maintain adequate habitat is generally lacking in the literature, as well as the role of episodic disturbances in supplying wood to rivers [ Miller et al ., ; Benda et al ., ; King et al ., ], despite the fact that the typical distribution of wood storage in relatively undisturbed rivers and streams might be used as the upper limit of what is ecologically useful. The range of values shown in Figures and is quite large, and it is a challenge for ecological research to define the lower limit of the volume of wood required to maintain ecological functioning in various environments.…”
Section: Advances In Quantifying Large Wood Budgetingmentioning
confidence: 99%